Downregulation of the CB1-Mediated Endocannabinoid Signaling Underlies D-Galactose-Induced Memory Impairment - Li, Ranran; Huang, Zhi; Luo, Juan; Luo, Hongyan; Wang, Wei (Frontiers in Molecular Neuroscience, 2020)
Imbalance in redox homeostasis is a major cause of age-related cognitive impairment. The endocannabinoid system (ECS) is a key player in regulating synaptic transmission, plasticity and memory. Increasing evidence indicates an important interplay between the two systems. However, how excessive oxidative stress could alter ECS and that, in turn, impairs its modulatory role in synaptic plasticity and cognitive function remains elusive. In the present study, we examined this causal link in D-galactose-induced oxidative rats. First, the reactive oxygen species generating enzymes, especially nitric oxide synthase (NOS), indeed show an elevated expression in D-galactose-treated rats, and this was correlated to an impaired hippocampal long-term potentiation (LTP) and spatial memory loss in animal behavioral tests. Second, the cannabinoid receptor type I (CB1)-mediated signing is known to regulate synaptic plasticity. We show that a decrease in CB1 and increase in degradation enzymes for CB1 ligand endocannabinoid anandamide all occurred to D-galactose-treated rats. Surprisingly, application of low-dose anandamide, known to reduce LTP under physiological condition, now acted to enhance LTP in D-galactose-treated rats, most likely resulted from the inhibition of GABAergic synapses. Furthermore, this reversal behavior of CB1-signaling could be fully simulated by a NOS inhibitor, diphenyleneiodonium. These observations suggest that interaction between redox dysfunction and ECS should contribute significantly to the impaired synaptic plasticity and memory loss in D-gal-treated rats. Therefore, therapies focusing on the balance of these two systems may shed lights on the treatment of age-related cognitive impairment in the future.